STRATEGI MEMBANGUN LOYALITAS DI KAWASAN INDUSTRI: PERAN KUALITAS LAYANAN, PERSEPSI HARGA DENGAN MEDIASI KEPUASAN - Ferry Kurniawati; Kristina Anindita Hayuningtias (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aims to analyze the effects of service quality and price perception on customer loyalty, with customer satisfaction acting as a mediating variable, at Wijayakusuma Industrial Estate. Customer loyalty is considered an important factor in maintaining long-term business relationships, occupancy stability, and the sustainability of industrial estate operations. The respondents consisted of 86 companies that have utilized the services of Wijayakusuma Industrial Estate. Data were collected through questionnaires and analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach. The results indicate that service quality and price perception have positive and significant effects on customer satisfaction. Service quality also has a positive and significant effect on customer loyalty, whereas price perception does not directly affect customer loyalty. Furthermore, customer satisfaction has a positive and significant effect on customer loyalty and serves as a mediating variable in the relationships between service quality and customer loyalty, as well as between price perception and customer loyalty. These findings highlight the importance of improving service quality and maintaining favorable price perceptions to enhance customer satisfaction and strengthen customer loyalty in the industrial estate sector.